(untitled) (Al-Qamar, 2023)
The sub-continent is one of Allah’s blessed lands, it is the Land of preachers, Scholars, Religion people, Traders, writers and poets. Arabs were aware of the importance of Sub-continent, because they used to travel to Subcontinent for trade before Islam. When Muhammad bin Qasim came for the purpose of conquering India, many scholars, writers, and poets came with him, and they exerted their efforts to spread Islam and the Arabic language, most of whom were religious scholars and Sufis, and among the most famous Arabic poets in the Indian subcontinent, Like Abu Atta Al-Sindi, Al-Biruni, Ata bin Yaqoub Al-Ghaznawi, and Sheikh Fakhr Al-Din Al-Iraqi. Sheikh Rukn al-Din al-Multani, Judge Abd al-Muqtadir al-Sharihi al-Kindi, Sheikh Ahmad al-Thansiri, Shah Wali Allah Mohaddith al-Dahlawi, Sayyed Ghulam Ali Azad al-Bilgrami, Sheikh Muhammad Saeed al-Sindi, and others. Sheikh Muhammad Saeed Al-Sindhi was a popular religious scholar, a famous Sufi, and a great and talented poet. He demonstrated his poetic talent in the three languages: Arabic, Persian, and Sindhi. He wrote his poems in Arabic and Persian. Indian and Arab scholars have praised his Broad expertise in the Arabic language and literature. He writes many poems in these two languages, which became famous in the Indian subcontinent because of his expertise. We find many literary virtues in his poems, such as the diverse words, structures, and styles. Beautiful pictures, deep imagination, music, etc.